Correlation between dynamic recrystallization and formation of rare earth texture in a Mg-Zn-Gd magnesium alloy during extrusion. Issue 1 (December 2018) - Jiang, M.; Xu, C.; Yan, H.; Lu, S.; Nakata, T.; Lao, C.; Chen, R.; Kamado, S.; Han, E.
Abstract The trace addition of rare earth (RE) elements in Mg alloys can modify the extrusion texture, leading to the formation of RE texture and thus improved formability. The interrupted extrusion experiment as well as electron back-scatter diffraction (EBSD) characterization was conducted in Mg-1.5Zn-0.5Gd (wt.%) alloy to unveil the dominant dynamic recrystallization (DRX) mechanism and its correlation with the formation of RE texture during extrusion. The results indicate that continuous DRX (CDRX) dominated the microstructural development. Fresh DRXed grains with 30° [0001] grain boundaries preferentially nucleated in unDRXed grains with [10 $$\bar{{\bf{1}}}$$ 1 ¯ 0] basal fiber orientation via CDRX, showing preferred selection of [2 $$\bar{{\bf{1}}}$$ 1 ¯ $$\bar{{\bf{1}}}$$ 1 ¯ 0] basal fiber orientation rather than RE texture orientation. Consequently, CDRX contributed to the weakening of [10 $$\bar{{\bf{1}}}$$ 1 ¯ 0] basal fiber texture and had a more significant effect on the formation of [2 $$\bar{{\bf{1}}}$$ 1 ¯ $$\bar{{\bf{1}}}$$ 1 ¯ 0] basal fiber component than that of RE texture component. Besides, the preferred growth of recrystallized grains with RE texture orientation was confirmed to occur during static annealing after extrusion, which is inferred as the key reason for the formation of RE texture in dilute Mg-RE alloys.